Le nationalisme catalan comme populisme : une approche des discours d’Artur Mas en 2014 - Jordi Canal (Conserveries Mémorielles)
The present Catalan nationalism, which predominantly embraced the independence solution, is populism. The real or symbolic confrontation or antagonism between two supposedly homogeneous entities, a "people", the Catalan people, and the "other", its enemy, the Spanish State or Madrid, lie at the foundations of Catalan nationalism. The speeches of Artur Mas as president of the Generalitat show it clearly.